2022
DOI: 10.3390/met12030401
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion Behavior of CoCrNi Medium Entropy Alloy in Simulated Seawater

Abstract: Understanding the fundamental behaviors of tribocorrosion for metals is critical for their possible application in seawater. For the recently emerging medium entropy alloys (MEAs), while mechanical wear and corrosion phenomena have been established, such experimental exploration is still lacking regarding the tribocorrosion behavior. In this work, the tribocorrosion behavior of CoCrNi MEA was investigated on a reciprocating sliding friction testing machine. Although a significant increase of current density fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Fe-25Cr-35Ni-based alloy undergoes dynamic recrystallisation (DRX) during high temperature tensile deformation. At small Z value (high tensile temperature and low strain rate), the DRX softening mechanism is easy to carry out [47]. When tensile deformation is carried out at high strain rate (a large Z value), the sliding time of dislocation is insufficient, and the DRX is difficult to achieve.…”
Section: Relationship Between Tensile Deformation Parameters and Micr...mentioning
confidence: 99%
“…Fe-25Cr-35Ni-based alloy undergoes dynamic recrystallisation (DRX) during high temperature tensile deformation. At small Z value (high tensile temperature and low strain rate), the DRX softening mechanism is easy to carry out [47]. When tensile deformation is carried out at high strain rate (a large Z value), the sliding time of dislocation is insufficient, and the DRX is difficult to achieve.…”
Section: Relationship Between Tensile Deformation Parameters and Micr...mentioning
confidence: 99%
“…Regarding the corrosion resistance, when the CoCrNi MEA and the CrMnFeCoNi HEA were analyzed comparatively in 0.1 M H2SO4 and 0.1 M NaCl, the MEA showed superior corrosion resistance [38]. Due to this behavior, the alloy could be used in ocean engineering structures as it was also shown that it exhibits superior passivity compared with 316L and Inconel 600 [39]. The CoCrNi alloy was also tested under an ultrahigh explosive loading rate to evaluate its suitability as a shaped charge liner, which could be used in many industries, A Fresh Perspective on Medium Entropy Alloys Applications as Coatings or Coating Substrate 37 such as oil, mining and construction.…”
Section: Meas As Structural Materialsmentioning
confidence: 99%
“…In addition, marine equipment contains many friction parts, including sea pumps, transmission shafts, etc. This means that metal materials will not only suffer corrosion but also suffer wear, and they will even suffer coupling damage of corrosion and wear (tribo-corrosion) in the marine environment [7][8][9]. The damage of metal materials greatly affects the safety and stability of marine equipment.…”
Section: Introductionmentioning
confidence: 99%